PENGGUNAAN MEDIA BERBASIS GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN PADA SISWA KELAS II SD NEGERI 2 ABEPURA - Lidya Eliabeth Sape; Dian Septikasari; Tiffany Shannaz Rusli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research sought to enhance foundational reading abilities of second-grade students at SD Negeri 2 Abepura by implementing image-based instructional media. The research was prompted by students' low reading proficiency, especially in letter recognition, syllable blending, and understanding simple sentences. The study utilized a Classroom Action Research (CAR) approach following the Kemmis and McTaggart model, conducted over two cycles that included stages of planning, implementation, observation, and reflection.The study included 31 second-grade students. data collection involved classroom observations, reading assessments, and documentation, which were examined using both qualitative and quantitative analyses.results showed significant progress in reading mastery: from 35.48% (11 students) in the pre-intervention phase to 64.51% (20 students) after Cycle 1, and 100% (31 students) after Cycle 2. Students also exhibited greater engagement and motivation.Reading skills were evaluated on four criteria: fluency, pronunciation accuracy, intonation, and comprehension. the media incorporated visuals inspired by Papuan local culture, making lessons more relatable and engaging. Improvements between cycles stemmed from refined lesson plans, enhanced visual quality, and interactive teaching methods. Instrument validity was confirmed via expert review, and reliability through Cronbach’s Alpha.In conclusion, image-based media proved an effective tool for developing foundational reading abilities in primary education.